Enumerating Atlantic salmon smolt production in River Vindelälven based on habitat availability and parr densities : consequences of using different density estimation methods - Ågren, Stefan (SLU/Dept. of Wildlife, Fish and Environmental Studies, 2010)
Habitat mapping was conducted in the main stem of River Vindelälven in the autumn of 2009 along the salmon distribution area. The aim was to estimate the quantity of potential reproduction areas, including spawning and juvenile rearing habitats. The mapping included 61 km of various stream sections along the river length of 269 km. The total area of stream habitats was estimated to 647 ha of which 396 ha (61%) were considered as either potential or optimal juvenile nursery habitats. The area of these two habitat classes were used to estimate the smolt production in the river by using electro fishing densities of juveniles (0+ per 100 m2). Data from the years 2001-2005 was used in four methods to estimate smolt production for the years 2005-2006. Method 1 was based on average 0+ density multiplied with the area of juvenile habitats. Method 2 was based on reach specific 0+ densities multiplied with reach specific juvenile areas. Method 3 was based on reach specific 0+ densities adjusted for flow conditions multiplied with specific juvenile areas and Method 4 was based on Method 1 using various hypothetical juvenile densities. All methods estimated the total no of 0+ salmons on the available habitats and these were used in an age structured Leslie matrix model to estimate the smolt production. Method 1 differed significant from both Method 2 and Method 3 however; there was no significant difference between Method 2 and Method 3. The smolt production was estimated to c. 30 000-60 000 where Method 1 estimated the highest smolt run. By using ArcGIS analyses of field based habitat mapping results (c. 600 ha) Method 1 estimated c. 91 000-94 000 smolt.